Legitimate peripheral participation of teachers in the implementation of CEFR-aligned classroom based assessment in Malaysian secondary schools / Anwar Farhan Mohamad Marzaini - Mohamad Marzaini, Anwar Farhan (2025)
Malaysia’s education has transformed due to the shift from an exam-centric culture to a more progressive assessment system. The enactment of Classroom Based Assessment signifies that the country is now moving towards enhancing the quality of the evaluation system. In the English language curriculum, the implementation of Common European Framework of Reference for Languages (CEFR) has garnered significant global attention because it infuses the new approach into the assessment system. According to the existing research, the effective execution of educational reform relies on the stakeholders’ understanding of the objectives of the curricular policy and their view of its relevance and practicality. Therefore, to shed light on this matter, the present study investigates the phenomena of internal stakeholders' Legitimate Peripheral Participation (LPP) in implementing the CEFR-Aligned Classroom-Based Assessment (CBA) in Malaysian schools. The LPP refers to the progressive integration of individuals into a community of practice through participation in peripheral activities, leading to eventual full participation in the community’s core practices. Hence, this study investigated how stakeholders participate in the new assessment practices by focusing on the dissemination process, the clarity and utility of curriculum documents, and the execution of assessment at the grassroots level. This research adopted a qualitative approach by utilising interviews, observations, and document analysis to gather data from the sample of 9 ESL teachers, 4 English Panel Heads and 2 curriculum trainers who were involved in the implementation of the new assessment. A total of 4 secondary English lessons were also observed and systemically analysed. Findings reveal a substantial challenge in realizing assessment reform within the Malaysian education system. Despite the widespread recognition of the reform’s potential to enhance the educational landscape, its implementation has fallen short of intended outcomes. The dissemination process and comprehensive curriculum documents, while wellintentioned, have not effectively catalysed teacher adoption of the reform. The resistance, stemming from a mismatch between teachers’ practices and beliefs and those advocated in the policy, has hindered their ability to assimilate new approaches. Consequently, the legitimacy of teachers in implementing the reform remains elusive. This study emphasises the importance of understanding the stakeholder participation in educational reform. By shedding light on the challenges faced in classroom assessment implementation, it provides insights crucial for policymakers and educations striving to bridge the gap between policy enactment and classroom practice. Addressing these challenges is essential for realizing the full potential of assessment reform and its impact on Malaysian education.